Linkage of strata of forest vegetation with forest soil microbiomes: a review - Gilliam, Frank S. (Frontiers in Microbiology, 2025)
A major dimension of pattern and process in ecological systems is the way in which species interact. In the study of forest communities, the phenomenon of linkage among forest strata (e.g., overstory and herbaceous layer) has been well investigated and arises when forest strata interact in ways that lead to causal connections between them. Whereas trees alter the light regime of forest herb communities, the herb layer can direct survivorship among seedlings of overstory species. Less studied, however, is linkage between forest strata and forest soil microbiomes. This review examines ways in which forest vegetation and soil microbiomes exert reciprocating effects on each other that can lead to linkage, beginning with a brief literature review of several phenomena relevant to how these effects occur. Because of the coincidence of the ubiquity of soil microbes with their almost infinitely small size, their interactions—both above and belowground in nature—with forest vegetation are particularly intimate. Although the most direct link, and certainly one that likely first comes to mind, is through root/microbe interactions, foliar surfaces and internal foliar tissues can support a diverse microbiome. Following the overview of potential mechanisms, examples from two separate forest studies of how linkage was demonstrated will be summarized. In each of these studies, linkage was evident through significant correlations among axis scores generated by canonical correspondence run separately for forest vegetation and soil microbial communities.